Quantitative Determination of Platelet Factor 3 Activity - Polasek, J; Duckert, F (Thrombosis and Haemostasis, 1971)
A method for the quantitative determination of platelet factor 3 (PF 3) is described. It is based on the prothrombin consumption and allows the determination of the total PF 3, of the PF 3 made available under various conditions and of PF 3 like activity.The material to be tested is recalcified in the presence of a normal PPP pool to maintain the intrinsic clotting factors in the optimal concentration range. After an appropriate incubation the coagulation is stopped by a citrate solution and the clot removed. The residual prothrombin activity in citrated serum is indirectly proportional to the PF 3 activity. This activity can be expressed in per cents by means of a reference curve which can be established with Cephaloplastin (Dade) dilutions. The 100% value is given by the total average PF 3 activity when the platelet count in PRP is adjusted to 100,000 platelets/mm3. An appropriate correction is needed when the prothrombin concentration is too low in the tested PRP.In 50 healthy blood donors the PF 3 activity ranged between 70-130% with quite small day to day variations.